Design and Implementation of a Rehabilitation Wireless Networked System - Mahmood Zaki Abdullah; Fadia Noori Hummadi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Many countries in the world do great efforts to achieve modern medical services to a lot of people; they applied modern network systems, electronic applications and programs to facilitate these issues. This paper will give a modern approach and algorithmic procedure for a rehabilitation system by using the modern aspects, techniques and protocols of the wireless networks. Firstly, an overview about previous works will be introduced then a proposal modern design for this system will be given, test and compare the obtained results with previous ones. A multi stage distributed servers will be used via this new design, this will assist and facilitate the ability of storage and delivering of the monitoring medical data, also checking for errors or damaged frames of data will be occurred at any stage.